Can declining energy intensity mitigate climate change? Decomposition and meta-regression results - Stephan B. Bruns; Christian Gross (Max Planck Institute of Economics, 2012)
Drawing on the Kaya identity, we assess the role of the main driver of the decline in carbon intensity, namely the (economic) energy intensity. Using meta-significance testing for a sample of 44 studies, dealing with the causality between energy and GDP, we find that both variables are strongly coupled. Hence, after having exhausted energy savings from nonrecurring structural changes, the economic energy intensity may soon converge than being arbitrarily reducible. We suggest, therefore, not to rely on further reductions of economic energy intensity but rather to invest in the reduction of the carbon intensity of energy to mitigate climate change.
Keywords: C83; Q43; Q51; 330; Climate change mitigation; Kaya identity; Energy intensity; Meta-significance testing; Klimaschutz; Energiekonsum; Faktorintensität; Energieeinsparung; Treibhausgas-Emissionen; Meta-Analyse